Evaluating the Role of Polymer Concrete in Enhancing Long-Term Performance and Reducing Early Age Cracking - Ahmad, Omar A.; Alkasassbeh, Abdelmajeed; Alma’aitah, Mohammad (Salehan Institute of Higher Education, 2025)
This study evaluates the potential of polymer concrete (PC) to reduce early-age cracking and improve long-term durability compared to traditional Portland cement concrete (PCC). It investigates the effect of varying polymer-to-aggregate ratios (5%-20%) on mechanical properties, early-age cracking, and durability under extreme environmental conditions, including freeze-thaw cycles, high temperatures, and chemical exposure. Experimental tests were conducted to measure compressive strength, flexural strength, fracture toughness, and durability of PC under accelerated aging conditions. The methodology involved mixing epoxy resin with selected aggregates to create different PC formulations. Tests such as restrained shrinkage, freeze-thaw, sulfuric acid immersion, and high-temperature exposure simulated real-world conditions. Results showed that PC with 15%-20% polymer content reduced early-age cracking by up to 56%, increased compressive strength by 28%, and exhibited superior resistance to freeze-thaw cycles and chemical degradation compared to PCC. The main contribution of this study is a comprehensive comparison between PC and PCC under accelerated aging, providing insights into the optimal polymer-to-aggregate ratio for maximizing performance and durability. These findings underscore the potential of polymer concrete as a durable, long-lasting material for high-performance infrastructure, especially in harsh environments. The research suggests that PC could extend the service life of concrete structures, lower maintenance costs, and offer a more sustainable alternative to traditional concrete.